The dynamics of the FDI-productivity nexus in BRICS: a wavelet coherence study - Malik, Avisha; Sah, Ash Narayan (Technological and Economic Development of Economy, 2025)
The current study investigates the interrelationship between FDI inflows and total factor productivity (TFP) in BRICS economies comprising Brazil, Russia, India, China, and South Africa, along with newly added members Egypt, Ethiopia, Iran, Saudi Arabia, and the UAE. Previous research has often overlooked the country-specific factors that influence how productivity impacts FDI inflows. To address this gap, the study introduces methodological innovation by employing the Method of Moments Quantile Regression (MM-QR) with fixed effects, using annual data from 2012 to 2022. This method accounts for unobserved heterogeneity, allowing for a detailed analysis of how TFP affects FDI across different countries and quantiles. The study adds novelty by utilising wavelet coherence analysis to explore co-movements and causal relationships between FDI and key macroeconomic variables at different time scales. The results show that FDI inflows have a positive and significant relationship with GDP and trade openness while exhibiting a negative association with TFP. Over the long term (16–32 weeks), coherence remains relatively weak, but TFP demonstrates a more consistent impact on FDI inflows compared to the other variables. The study recommends that BRICS nations should enhance FDI’s impact by improving trade integration and regional cooperation to attract high-value investments and foster sustainable growth. First published online 24 September 2025